Late infantile acid maltase deficiency: a case report - Mine Çalışkan; Yüksel Yılmaz; Piraye Serdaroğlu; Nur Aydınlı; Meral Özmen (The Turkish Journal of Pediatrics, 1999)
A five-year-old boy with late-infantile (juvenile) form of acid maltase deficiency is presented. His symptoms were restricted to skeletal muscle. There is commonly a correlation between the amount of residual acid maltase activity and the severity of the clinical picture. Although the residual enzyme level was very low in our patient, no progression of his neurological findings have been observed during the follow-up period of two years.